Strengthening Islamic Moderation Education through Extracurricular Activities in High Schools - Karisma Ayu Candra (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Religious moderation education is a key strategy in shaping a young generation that is tolerant, inclusive, and respectful of diversity. This study aims to analyze the role of extracurricular activities in strengthening Islamic moderation values in high schools. Extracurricular programs such as Islamic Spirituality (Rohis), scouting, and student organizations are considered effective platforms for internalizing moderation values through collaborative approaches, critical discussions, and the habituation of inclusive attitudes. This research employs a descriptive qualitative method by collecting data through observation, interviews, and document analysis in several high schools. The findings reveal that well-structured extracurricular activities significantly enhance students' understanding of Islamic moderation principles, including tawasuth (middle path), tasamuh (tolerance), and i’tidal (justice). Moreover, the active involvement of teacher advisors and inter-organizational collaboration within schools serve as key supporting factors for the success of this program. This study emphasizes the importance of integrating religious moderation values into non-formal school activities as a preventive effort against intolerance among adolescents.